Success factors and barriers to the effective debt collection process - Łada, Monika; Wejer-Kudełko, Małgorzata (Research Papers of Wrocław University of Economics, 2018)
The paper analyses the problem of a debt collection process perceived from legal, economic and psychosociological perspective. The aim of this article is to present the key success factors and barriers to the effective debt collection process. The list of these factors is based on a conducted research among the companies operating on Polish market in business-to-business sector. According to the findings from the survey, it turned out that the most important changes are to be made especially in legal sphere but economic and psychosociological issues also need to be considered
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 515; s. 147-156
Keywords: debt collection; effectiveness; process; success factors; barriers; windykacja należności; proces; skuteczność; czynniki sukcesu; bariery